«The steamer started moving, the music began to play ...»: son of military expert of the Red Army M. N. Artamonov on the journey from Omsk to Obdorsk (1922) - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
This archaeographic publication is devoted to the life of Western Siberia in the early 1920s. The purpose of the work is to present the daily life of the region and aspects of the life of the former general staff and his family in Soviet Russia as an example of a fragment of M. N. Artamonov’s diary — the son of a military specialist of the Red Army. In the practice of studying the situation of the former whites after the Civil War, archaeographic work, as a result of research, is rare. The relevance of this work is seen in the fact that the publication of sources of personal origin allows a fuller study of the life of the family of the former general staff in Soviet Russia, the life of those years. The publication may be of interest to researchers studying the everyday aspects of the life of Soviet society and the military history of the 1920s